The Happiness Gains From Sorting and Matching in the Labor Market - Simon Luechinger; Alois Stutzer; Rainer Winkelmann (University of Basel, Center of Business and Economics (WWZ), 2007)
Sorting of people on the labor market not only assures the most productive use of valuable skills but also generates individual utility gains if people experience an optimal match between job characteristics and their preferences. Based on individual data on subjective well-being it is possible to assess these latter gains from matching. We introduce a two-equation ordered probit model with endogenous switching and study self-selection into government and private sector jobs. In an analysis with data from the European Social Survey, we find considerable gains from matching amounting to an increase in the fraction of very satisfied workers from 53.8 to 58.8 percent relative to a hypothetical random allocation of workers to the two sectors. A companion analysis of data from the German Socio-Economic Panel shows that selection on unobservables is reduced once we include additional controls for preference heterogeneity.
Keywords: D60; I31; J24; J45; 330; Matching; ordered probit; public sector employment; selection; switching regression; subjective well-being; Zufriedenheit; Lebensqualität; Arbeitsmarkt; Vergleich; Öffentlicher Dienst; Privatwirtschaft; Matching; Schätzung; Europa; Deutschland